Development of the technological character of the work performed in improving the state cadastre system of forestry - Muzropova, Fazilat Ibrohim qizi; Baratova, Maftuna Zafar qizi (Science and Education, 2023)
It serves to increase the layer of users of these services by improving the automated system of maintaining the cadastre of forest areas, expanding forest areas and systematic registration of trees in it, filling the database, providing forest lands, and makes it possible to direct funds allocated by the state budget to the development of the cadastral sector to the forestry sector.